Healing Uncured Wounds Through Forgiveness (Hekima Review, 2016)
The world has been characterized these last decades by several protracted conflicts that had negative impacts on the everyday life of civil and local populations. Some triggered ethnic-based violence and killings, massive and gang rapes on women and children, huge displacements of people, and so on. A number of victims have been assisted and accompanied in various ways; still wounds remain fresh and uncured. The period from December 8, 2015 to November 20, 2016 has been proclaimed by Pope Francis an Extraordinary Jubilee of Mercy. On the Pope’s evidence, the relevance of this Jubilee now lays on the fact that “this is the time for mercy, the favorable time to heal wounds, a time to offer everyone the way of forgiveness and reconciliation.” This paper assesses the role forgiveness – as a way of living mercy – can play in healing victims’ wounds and reconciling them with themselves, their persecutors, and their Creator.